2017
DOI: 10.1016/j.bmcl.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Triazole-linked fluorescent bisboronic acid capable of selective recognition of the Lewis Y antigen

Abstract: Cell surface carbohydrates of the Lewis blood group antigens, Lewis X (Le), Lewis Y (Le), Lewis A (Le), and their sialylated derivatives, such as sialy Lewis X (sLe) and sialy Lewis A (sLe), play important roles in various recognition processes. These cell surface carbohydrates have also been associated with the development and progression of many types of cancers. Recently, we synthesized four anthracene-based fluorescent bisboronic acid sensors (compounds 2a-d) linked by 'click' chemistry with tethers of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…80 It was found that the uorescence of 30a increased aer binding to sialyl Lewis Y. The result indicates that 30a has a high sensitivity and selectivity for sialyl Lewis Y.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…80 It was found that the uorescence of 30a increased aer binding to sialyl Lewis Y. The result indicates that 30a has a high sensitivity and selectivity for sialyl Lewis Y.…”
mentioning
confidence: 73%
“…Wang et al synthesized four anthracene-based fluorescent diboronic acid sensors (30a–d) and examined the selectivity of different length linkers for sialyl Lewis. 80 It was found that the fluorescence of 30a increased after binding to sialyl Lewis Y. The result indicates that 30a has a high sensitivity and selectivity for sialyl Lewis Y.…”
Section: Carbohydrates Boronic Acid Sensorsmentioning
confidence: 91%
“…Also harnessing the power of click chemistry, in 2017 Wang et al produced a series of four fluorescent bis-boronic acids targeting the Lewis group of cell-surface tetrasaccharides, 37a – d , Figure . In essence, two of the Shinkai and co-workers’ PBA-anthracene-type systems are appended with different linker lengths and are “clicked” together about a triazole core.…”
Section: Boronic Acid-based Saccharide Sensor Designmentioning
confidence: 99%
“…Compound 7 , with a longer linker (∼10 nm) was ineffective, with higher MICs and loss of specificity for mycobacteria. Multivalent presentation of boronic acids has been reported to lead to increased binding affinities,22 and the nature and length of the linker has been demonstrated in other studies to have a large influence on boronic acid binding selectivity and affinity and is likely to be important here 23. The increased activity of the shorter linkers would support a chelation mechanism to the cell glycans (see below for experimental evidence of binding).…”
Section: Resultsmentioning
confidence: 88%